Participatory mapping, learning and change in the context of biocultural diversity and resilience - Ali, Million Belay (Rhodes University, Faculty of Education, Department of Education, 2012)
This study set out to investigate the learning and change that emerged in and through participatory mapping in the context of biocultural diversity and resilience in rural Ethiopia. It did this through examining the learning and agency emerging from three participatory mapping practices (Participatory 3 Dimensional Modelling, sketch mapping and eco-cultural calendars) using two case study sites, located in the Bale Mountains and the Foata Mountains in Ethiopia, and honing in on in-depth reflective processes in two community contexts located within the broader case study sites, namely Horo Soba, Dinsho wereda in Bale; and Telecho, in Wolmera wereda, in the Foata Mountain complex. This study tried to answer three research questions related to participatory mapping: its role in mobilizing knowledge related to biocultural landscape, its role in learning and change, and its value in building resilience. The study used qualitative case study research methodology underpinned by critical realist philosophy, and used photographic 'cues' to structure the reporting on the cases. It used four categories of analysis: biocultural diversity, educational processes, learning and agency, in the first instance to report on the interactions associated with the participatory mapping practices as they emerged in the two case study sites. This was followed by in-depth analysis and interpretation of participatory mapping and biocultural diversity, as well as participatory mapping and learning, with an emphasis on acquisition, meaning making and identity formation processes. The in-depth analysis drew on social and learning theory, and theory of biocultural diversity and social-ecological resilience. The study also included analysis of broader change processes that were related to and emerged from the social interactions in the mapping activities, and the resultant morphogenesis (change), showing that morphogenesis, while broadly temporal, is not linear, and involves 'little iterative morphogenic cycles'. These insights were then used to interpret how participatory mapping may contribute to resilience building in a context where social-ecological resilience is increasingly required, such as the two case study sites, where socialecological degradation is highly visible and is occurring rapidly. The study's contribution to new knowledge lies in relation to the role of participatory mapping in facilitating learning, agency and change which, to date, appears to be under-theorised and under-developed in the participatory mapping and environmental education literature. As such, the study findings provide in-depth insight into how participatory mapping methodologies may 'work in the world', in contexts such as those presented in the two cases under study. It has tried to demonstrate how participatory mapping has managed to mobilize knowledge related to biocultural diversity, facilitated the acquisition of knowledge and helped members of the community to engage in meaning making activities relevant to their biocultural landscape and renegotiate their identity within the wider community context. It has also shown that dissonance is an important dynamic in the learning process; and that morphogenesis (or change) occurs over time, but also in smaller cycles that interact at different levels; and that participatory mapping cannot, by itself mobilise significant structural change, at least in the short term. It has also shown, however, that learning and the desire for change can emerge from participatory mapping processes, and that this can be utilized to adapt to the changing socio-ecological environments, potentially contributing to longer term resilience of social-ecological systems.
Keywords: Biodiversity conservation -- Research -- Ethiopia; Cultural pluralism -- Research -- Ethiopia; Ethnopsychology -- Research -- Ethiopia; Adult education -- Research -- Ethiopia